ALPHA-CTX is associated with subchondral bone turnover and predicts progression of joint space narrowing and osteophytes in osteoarthritis - Huebner, Janet L (2014)
OBJECTIVE: To evaluate joint tissue remodeling, with urinary collagen biomarkers, uALPHA CTX and uCTXII, and their association with osteoarthritis (OA) severity, progression, and localized knee bone turnover. METHODS: Participants (N=149) with symptomatic and radiographic knee OA underwent fixed flexion knee radiography at baseline and 3 years, and late-phase bone scintigraphy of both knees at baseline, scored semi-quantitatively for osteophyte (OST) and joint space narrowing (JSN) severity and uptake intensity with scores summed across knees. Urinary concentrations of ALPHA CTX and CTXII were determined by ELISA. Immunohistochemistry of human OA knees was performed to localize the joint tissue origin of the biomarker epitopes. RESULTS: uALPHA CTX correlated strongly with intensity of bone scintigraphic uptake, and JSN and OST progression (risk ratio=13.2 and 3, respectively). uCTXII was strongly associated with intensity of bone scintigraphic uptake, with JSN and OST severity, and OA progression based on OST. uALPHA CTX localized primarily to high bone turnover areas in subchondral bone; CTXII localized to the bone-cartilage interface, the tidemark, and damaged articular cartilage. CONCLUSION: Baseline uALPHA CTX, localized to high turnover areas of subchondral bone, was associated with dynamic bone turnover of knees signified by scintigraphy, and progression of both OST and JSN. uCTXII correlated with JSN and OST severity, and progression of OST. To our knowledge, this represents the first report of serological markers reflecting subchondral bone turnover. These collagen markers may be useful for non-invasive detection and quantification of active subchondral bone turnover and joint remodeling in knee OA.